40. Uranium Deposits of Wyoming and South Dakota - E. N. Harshman (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1968)
Uranium mining and milling are rather new industries in Wyoming and South Dakota, but, in the past 15 years, ore valued at more than $400,000,000 has been mined and milled in the region. The major uranium deposits are in structural and/ or erosional basins or on the flanks of uplifts. The principal host rocks are medium- to coarse-grained sandstones that were deposited in continental or brackish-water environments and were derived in large part from the granitic cores of the uplifts and the sedimentary rocks that flank the cores. The ages of the host rocks range from Cretaceous to Miocene, but more than 95 per cent of the known reserves in the region are in rocks of early Eocene age. The bulk of the ore in the region is unoxidized and lies below the water table; some oxidized ore has been mined in the Powder River Basin and Black Hills districts. The unoxidized ore comprises pyrite, uraninite and/ or coffinite, marcasite, hematite, jordisite(?), and selenium. Minerals in the oxidized ore include hydrous uranium carbonates, phosphates, and sulfates and hydrous uranium and/ or vanadium silicates. The deposits are in the form of ore rolls that contain from a few hundred to a few hundred thousand tons of ore, ranging in grade from 0.1 per cent to 1.0 per cent U3O8. The rolls are at the margins of large tabular bodies of sandstone that has been altered by the orebearing solutions. The deposits are believed to have resulted from the interaction of an alkaline; oxidizing, ore-bearing ground water and a reducing environment. Exploration guides include the spatial relations of ore to altered sandstone, favorable lithology in the host rock, the content of certain elements and/ or compounds in ground water, and the relation of deposits to major paleodrainages.